Improved Dielectric, Magnetic, and Multiferroic Properties of (Bi0.5Na0.5)0.7La0.3(Ti0.7Fe0.3)O3 Ceramics Synthesis by the Solid‐State Combustion Technique - Chittakorn Kornphom; Widchaya Somsri; Sasipohn Prasertpalichat; Bhoowadol Thatawong; Chatchai Kruea‐In; Thanya Udeye; Aurawan Rittidech; Chanagon Menkun; Naratip Vittayakorn; Supree Pinitsoontorn; Pongsakorn Jantaratana; Narong Chanlek; et al. (physica status solidi (a), 2024)
Lead‐free (Bi 0.5 Na 0.5 ) 0.7 La 0.3 (Ti 0.7 Fe 0.3 )O 3 ceramics (abbreviated as BNLTF) are synthesized by the solid‐state combustion technique using glycine as fuel. The effect of the firing temperature (calcined between 700 and 800 °C for 2 h and sintered between at 800 and 900 °C for 2 h) on the phase structure, microstructure, electrical, and magnetic properties is investigated. Pure BNLTF powders are obtained with a calcination temperature of 750 °C for 2 h and the crystal size increases from 47 to 62 nm when the calcination temperature increases from 700 to 800 °C. All sintered BNLTF ceramics show a pure perovskite structure with a rhombohedral phase. The average grain size increases with increasing sintering temperatures. A well‐packed microstructure with the highest density (5.98 g cm −3 ), good dielectric properties at room temperature ( ε r ≈ 589 and tan δ ≈ 0.572), soft ferroelectric behavior, and excellent magnetic properties ( M s ≈ 0.091 emu g −1 , M r ≈ 0.0026 emu g −1 ) is obtained from the ceramic sintered at 875 °C for 2 h. The multiferroic BNLTF ceramic sintered at 875 °C has a maximum magnetoelectric coupling coefficient ( α E ≈ 2.08 mV cm −1 Oe −1 ) when the magnetic field is near 4500 Oe.
Keywords: Ferroelectric and Piezoelectric Materials; Multiferroics and related materials; Dielectric properties of ceramics